Penggunaan Metode Bercerita Terhadap Perkembangan Keterampilan Berbicara pada Anak Usia 5-6 Tahun di TK Dharma Wanita Persatuan Provinsi Bengkulu - Seni Parantika; Irwan Satria; Abdul Aziz Mustamin (Yayasan Darusssalam Bengkulu, 2025)
This study aims to 1) describe how the storytelling method affects speech delay in children at Dharma Wanita Persatuan Kindergarten, Bengkulu Province, 2) to describe the parenting pattern of parents towards children at Dharma Wanita Persatuan Kindergarten, Bengkulu Province who experience speech delay, and 3) to describe the factors that influence speech delay in group B children at Dharma Wanita Persatuan Kindergarten, Bengkulu Province. This study uses a descriptive qualitative field research method. The location of the study was at Dharma Wanita Persatuan Kindergarten, Bengkulu Province. The research subjects included teachers, principals, and 2 speech delay students at Dharma Wanita Persatuan Kindergarten, Bengkulu Province. Data collection was carried out through observation, interviews, and documentation. The results of the study showed that the storytelling method applied by teachers consistently, especially by using visual media such as picture story books, can significantly stimulate children's speaking abilities. In addition, it was found that the permissive parenting pattern applied by some parents contributed to low language stimulation at home, which resulted in speech delay. Health, neurological factors, and the structure and physiology of children also affect children's ability to respond to and process the information received. Thus, handling speech delays in early childhood needs to involve a holistic approach, including the active role of teachers, appropriate parenting patterns, and attention to aspects of child development as a whole.